Unconditional Cash Transfers in China : Who Benefits from the Rural Minimum Living Standard Guarantee (Dibao) Program? - Golan, Jennifer; Sicular, Terry; Umapathi, Nithin (Elsevier, 2018)
This paper analyzes China’s rural minimum living standard guarantee (dibao) program, one of the largest minimum income cash transfer schemes in the world, and examines possible changes to the program design. Despite its size and central position in China’s current poverty reduction strategy, little is known about the rural dibao program’s performance and targeting effectiveness. Our analysis uses annual household survey data from the China Household Income Project matched with published administrative data for the years 2007–09. We find that the program provides sufficient income to poor beneficiaries but does not substantially reduce the overall level of poverty. Conventional targeting analysis reveals large inclusionary and exclusionary targeting errors; propensity score targeting analysis yields smaller but still large targeting errors. Simulations of possible changes to the program design reveal that expanding coverage can potentially yield greater poverty reduction than increasing transfer amounts. Replacing locally diverse dibao lines and transfer amounts with a nationally uniform dibao threshold and transfer could in theory reduce poverty further, but the potential gains are modest without improvements in targeting. This paper makes several contributions. To our knowledge this is the first household-level empirical analysis of China’s dibao program in rural areas, so the findings provide new, policy-relevant information. Moreover, the literature has not settled the question of whether such programs should be centralized or decentralized. We show that in practice the potential gains of centralizing the eligibility rule and transfer amount are conditional on the efficiency of targeting. By varying the program’s key design parameters our analysis also yields insights into alternative policy recommendations to improve the program performance.